Studies on Genetic Divergence among Greengram (Vigna radiata L.) Germplasm Accessions - Sridhar, V.; Rao, S. Srinivasa; Sriram, A.; Gopal, G.Venu (International Journal of Bio-resource and Stress Management, 2022)
The present study was conducted at the Agricultural Research Station, Madhira, Telangana, India during rabi (October−December), 2017–18 to evaluate 39 diverse greengram germplasm accessions. The experiment was laid out in RBD replicated twice for 8 quantitative traits to study the nature and magnitude of genetic diversity among the accessions by multivariate analysis such as cluster analysis with D2 Statistics and principal component analysis. 3 principal components viz., PC I, PC II and PC III contributed about 85.45% of total variance for the genotypes studied. The genotypes were grouped into 8 distinct clusters of which cluster I is the largest with a maximum number (16) of genotypes followed by cluster II and cluster VI with 6 genotypes each. Genotypes IC-436735, IC-261261, WGG-42 representing mono genotypic cluster signifies presence of diversity for creating variability through hybridization. Highest intra cluster distance of 47.27 was recorded for cluster VI and highest inter-cluster distance of 252.46 was observed between cluster IV and VIII. Data on cluster means for various traits showed that the highest mean value for number of clustersplant-1, number of pods plant-1 and seed yield plant-1 was recorded by cluster VII. Percent contribution revealed that plant height contributed the most (32.11%) followed by seed yield plant-1 (21.86%) for total genetic divergence. The genotypes in the clusters with maximum inter cluster distance may be used as potential parents for developing high yielding greengram cultivars.